Biaxially stretched polyamide film and laminated film
By using partially biomass-derived polyamide resins and polyamide 6 resins from biomass in the biaxially stretched polyamide film, and using specific laminated structures and additive ratios, the contradiction between the film's bending resistance and friction-resistant pinhole resistance is solved, and a high-performance carbon neutral packaging film is achieved.
Patent Information
- Application Number
- CN202411829843.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-17
- Filing Date
- 2020-01-24
- Publication Date
- 2025-03-07
AI Technical Summary
There is a contradiction between the existing biaxial stretched polyamide films and the friction-resistant pinhole properties. Improvement will reduce the performance on the other hand. At the same time, thermal deterioration of the polyamide-based elastomer during the manufacturing process leads to grease accumulation problems on the orifice, affecting the accuracy and production efficiency of the film thickness.
A biaxially stretched polyamide film consisting of polyamide 6 resin and a partially biomass-derived polyamide resin is used, and the bending pinhole resistance and friction pinhole resistance of the film are improved through a specific laminated structure and additive ratio, while avoiding thermal deterioration of the polyamide-based elastomer.
The impact resistance, bending pinhole resistance and friction pinhole resistance of the biaxially stretched polyamide film are achieved simultaneously, which extends the continuous production time of the film, reduces the risk of deterioration adhesion, and the use of biomass materials can help carbon neutrality.
Smart Images

Figure CN119567689A_ABST
Abstract
Description
[0001] This application is a divisional application. The filing date of the parent application is January 24, 2020. The international application number is PCT / JP2020 / 002534. The application number entering the Chinese national phase is 202080015003.6. The name of the invention is biaxially stretched polyamide film and laminated film. Technical Field
[0002] The present invention relates to a carbon-neutral biaxially stretched polyamide film which has excellent impact resistance, bending pinhole resistance and friction pinhole resistance and uses a raw material derived from biomass (organic resources derived from organisms such as plants). The biaxially stretched polyamide film of the present invention is suitable for use as a food packaging film, etc. Background Art
[0003] Conventionally, biaxially stretched films made of aliphatic polyamides represented by polyamide 6 are excellent in impact resistance and bending pinhole resistance and are widely used as various packaging material films.
[0004] In order to further improve the bending pinhole resistance and impact resistance for liquid-filled packaging such as soups and seasonings, biaxially stretched polyamide films are widely used, which are made more flexible and have improved bending pinhole resistance by blending various elastomers (rubber components) into aliphatic polyamide.
[0005] As a means of improving the above-mentioned bending pinhole resistance, a film obtained by mixing aliphatic polyamide with a polyamide-based elastomer is known (for example, see Patent Document 1). This film has good bending pinhole resistance and impact resistance in a low temperature environment, and is unlikely to produce pinholes caused by bending fatigue even in a low temperature environment.
[0006] However, pinholes are not only generated by bending, but also by friction (abrasion). The improvement methods for pinholes caused by bending and pinholes caused by friction are often opposite. For example, there is a tendency that if the softness of the film is increased, bending pinholes are difficult to generate, but the softer it becomes, the easier it is to generate pinholes caused by friction. In response to this, it is proposed that a laminate for packaging with excellent bending resistance and friction pinhole resistance is provided by providing a surface coating agent on the outer surface of a biaxially stretched polyamide film (for example, refer to Patent Document 2). However, this method has little effect in preventing the generation of friction pinholes. In addition, a coating process becomes necessary.
[0007] In addition, in the case of a film in which an aliphatic polyamide is mixed with a polyamide-based elastomer, due to thermal degradation of the polyamide-based elastomer added during film production, a degradation product called orifice buildup (Japanese: me yani) is likely to be generated at the die lip outlet. Also, it is known that the degradation product causes deterioration in the accuracy of the film thickness. In addition, the degradation product has the following problems: defective products are produced due to its own dropping, and the production efficiency during continuous film production is reduced.
[0008] In recent years, in order to build a recycling-based society, attention has been paid to the following aspect: using biomass as a raw material to replace fossil fuel raw materials in the material field. Biomass is an organic compound obtained by photosynthesis of carbon dioxide and water, and is a raw material for so-called carbon neutrality (since the amount of carbon dioxide discharged into the environment is the same as the amount absorbed, an increase in carbon dioxide as a greenhouse gas can be suppressed) that becomes carbon dioxide and water again by using this organic compound. Recently, the practical application of biomass plastics using such biomass as a raw material has rapidly developed, and attempts have also been made to manufacture polyesters, which are general-purpose polymer materials, from these biomass raw materials.
[0009] For example, in Patent Document 3, in the field of polyester films, a resin composition and a film are disclosed. The resin composition is characterized by containing a polyester formed from a glycol unit and a dicarboxylic acid unit, and containing 50 to 95% by mass of a polyester in which the glycol component unit is ethylene glycol derived from biomass and the dicarboxylic acid component unit is a dicarboxylic acid derived from petroleum with respect to the whole resin composition.
[0010] According to this technology, even for a polyester manufactured by using ethylene glycol derived from biomass in place of the existing ethylene glycol obtained from fossil fuels, mechanical properties equivalent to those in the case of using ethylene glycol derived from fossil fuels can be obtained.
[0011] Against this background, a carbon-neutral raw material using a biomass-derived raw material is also sought in polyamide films.
[0012] Prior Art Documents
[0013] Patent Documents
[0014] Patent Document 1: Japanese Patent Laid-Open No. 11-254615
[0015] Patent Document 2: Japanese Patent Laid-Open No. 2001-205761
[0016] Patent Document 3: Japanese Patent Laid-Open No. 2012-097163 Summary of the Invention
[0017] Problems to be Solved by the Invention
[0018] The present invention was created in view of the problems of the above-mentioned prior art. The object of the present invention is to provide a biaxially stretched polyamide film that is excellent in impact resistance, flexing pinhole resistance, and friction pinhole resistance, and is carbon-neutral using raw materials derived from biomass.
[0019] Means for Solving the Problems
[0020] That is, the present invention includes the following configurations.
[0021] [1] A biaxially stretched polyamide film, characterized by containing 99 to 70% by mass of polyamide 6 resin and 1 to 30% by mass of a polyamide resin at least part of the raw materials of which is derived from biomass.
[0022] [2] A biaxially stretched polyamide film, characterized in that a B layer (surface layer) is laminated on at least one surface of an A layer (base material layer), the A layer contains 99 to 70% by mass of polyamide 6 resin and 1 to 30% by mass of a polyamide resin at least part of the raw materials of which is derived from biomass, and the B layer contains 70% by mass or more of polyamide 6 resin.
[0023] [3] The biaxially stretched polyamide film according to the above [1] or [2], characterized in that the content of carbon derived from biomass measured by radiocarbon (C 14 ) in all the carbon in the above biaxially stretched polyamide film is 1 to 15%.
[0024] [4] The biaxially stretched polyamide film according to any one of [1] to [3], characterized in that the polyamide resin at least part of the raw materials of which is derived from biomass is at least one polyamide resin selected from the group consisting of polyamide 11, polyamide 410, polyamide 610, and polyamide 1010.
[0025] [5] The biaxially stretched polyamide film according to any one of [1] to [4], characterized by satisfying the following (a) and (b):
[0026] (a) The number of Gelbo pinhole defects when the torsional bending test (Japanese: ひねり屈曲試験) using a Gelbo torsion tester is carried out 1000 times at a temperature of 1°C is 10 or less;
[0027] (b) The distance until a pinhole is generated in the friction pinhole test is 2900 cm or more.
[0028] [6] The biaxially stretched polyamide film according to any one of [1] to [5], characterized in that the haze is 10% or less and the dynamic friction coefficient is 1.0 or less.
[0029] [7] The biaxially stretched polyamide film according to any one of [1] to [6], characterized in that the lamination strength after being laminated with a polyethylene-based sealing film is 4.0 N / 15 mm or more.
[0030] [8] A laminated film in which a sealing film is laminated on the biaxially stretched polyamide film according to any one of [1] to [7].
[0031] [9] A packaging bag using the laminated film described in [8].
[0032] Advantages of the Invention
[0033] The biaxially stretched polyamide film of the present invention uses polyamide 6 resin as the main component, incorporates a polyamide resin obtained by polymerizing a raw material derived from a specific biomass, and adopts specific film-forming conditions, thereby enabling the production of a polyamide film that exhibits impact resistance, flexing pinhole resistance, rubbing pinhole resistance, adhesiveness to a sealing film, and is carbon neutral.
[0034] In addition, in the present invention, different from the conventional polyamide-based elastomer added to improve flexing pinhole resistance, since the polyamide-based elastomer does not deteriorate inside the die, it is possible to suppress the attachment of deteriorated products to the inner surface of the die and the attachment of die lip build-up to the die lip outlet for a long time. As a result, it is possible to prevent the deterioration of film thickness unevenness.
[0035] In addition, if deteriorated products adhere to the inner surface of the die or the die lip outlet, the thickness unevenness deteriorates, and thus it is necessary to stop production and clean the die lip. The biaxially stretched polyamide film of the present invention enables continuous production for a long time. Description of the Drawings
[0036] Figure 1 Schematic diagram of a rubbing pinhole resistance evaluation device
[0037] Explanation of Reference Numerals
[0038] 1: Head of the fastness testing machine
[0039] 2: Corrugated cardboard
[0040] 3: Liner paper for holding the sample
[0041] 4: Film sample folded in two (Japanese: four-fold)
[0042] 5: Rubbing amplitude direction Detailed Description of the Invention
[0043] Hereinafter, the biaxially stretched polyamide film of the present invention will be described in detail.
[0044] The biaxially stretched polyamide film of the present invention is: a biaxially stretched polyamide film comprising 99 to 70% by mass of a polyamide 6 resin and 1 to 30% by mass of a polyamide resin of which at least a part of the raw material is derived from biomass; or a biaxially stretched polyamide film in which a surface layer (B layer) is laminated on at least one side of a base layer (A layer) comprising 99 to 70% by mass of a polyamide 6 resin and 1 to 30% by mass of a polyamide resin of which at least a part of the raw material is derived from biomass.
[0045] [Biaxially stretched polyamide film or substrate layer (layer A)]
[0046] The biaxially stretched polyamide film or substrate layer (layer A) of the present invention contains 70% by mass or more of the polyamide 6 resin, thereby achieving excellent mechanical strength such as impact strength inherent in the biaxially stretched polyamide film containing the polyamide 6 resin and gas barrier properties against oxygen and the like.
[0047] The biaxially stretched polyamide film or substrate layer (A layer) of the present invention includes 1 to 30% by mass of a polyamide resin in which at least a portion of the raw material is derived from biomass, thereby improving the bending pinhole resistance. In the case of polyamide elastomers and polyolefin elastomers used as improvers for bending pinhole resistance in the past, although the bending pinhole resistance is improved, the friction pinhole resistance is deteriorated. By including 1 to 30% by mass of a polyamide resin in which at least a portion of the raw material is derived from biomass, a biaxially stretched polyamide film having excellent bending pinhole resistance and friction pinhole resistance can be obtained. In addition, a carbon-neutral film having little effect on the increase or decrease of carbon dioxide on the ground can be obtained.
[0048] [Polyamide 6 resin]
[0049] The polyamide 6 resin used in the present invention is generally produced by ring-opening polymerization of ε-caprolactam. The polyamide 6 resin obtained by ring-opening polymerization is generally melt-extruded by an extruder after removing lactam monomers with hot water, followed by drying.
[0050] The relative viscosity of the polyamide 6 resin is preferably 1.8 to 4.5, more preferably 2.6 to 3.2. When the relative viscosity is less than 1.8, the impact strength of the film is insufficient. When it is greater than 4.5, the load on the extruder becomes large, making it difficult to obtain an unstretched film before stretching.
[0051] [Polyamide resin at least part of which is derived from biomass]
[0052] Examples of the polyamide resin at least part of which is derived from biomass as a raw material used in the present invention include polyamide 11, polyamide 410, polyamide 610, polyamide 1010, polyamide MXD10 resin, and polyamide 11 / 6T copolymer resin.
[0053] Polyamide 11 is a polyamide resin having a structure in which monomers having 11 carbon atoms are bonded via amide bonds. Generally, polyamide 11 is obtained using aminoundecanoic acid or undecanoic acid as a monomer. In particular, aminoundecanoic acid is a monomer obtained from castor oil, and is therefore ideal from the viewpoint of carbon neutralization. The structural units derived from the monomers having 11 carbon atoms in polyamide 11 are preferably more than 50% of all structural units, more preferably more than 80%, and may also be 100%.
[0054] The polyamide 11 is generally produced by polymerizing the aminoundecanoic acid. The polyamide 11 obtained by polymerization is dried after lactam is removed with hot water as needed, and then melt-extruded with an extruder.
[0055] The relative viscosity of polyamide 11 is preferably 1.8 to 4.5, more preferably 2.4 to 3.2. When the relative viscosity is less than 1.8, the impact strength of the film is insufficient. When it is greater than 4.5, the load on the extruder becomes large, making it difficult to obtain an unstretched film before stretching.
[0056] The above-mentioned polyamide 610 is a polyamide resin having a structure formed by polymerization of a diamine having 6 carbon atoms and a dicarboxylic acid having 10 carbon atoms. Usually, hexamethylenediamine and sebacic acid are used. Among them, sebacic acid is a monomer obtained from castor oil, and is therefore ideal from the viewpoint of carbon neutralization. These structural units derived from monomers having 6 carbon atoms and structural units derived from monomers having 10 carbon atoms are in PA610, and their total is preferably 50% or more of all structural units, more preferably 80% or more, and may also be 100%.
[0057] The above-mentioned polyamide 1010 is a polyamide resin having a structure in which a diamine having 10 carbon atoms and a dicarboxylic acid having 10 carbon atoms are polymerized. Generally, polyamide 1010 uses 1,10-decanediamine (decamethylenediamine) and sebacic acid. Decamethylenediamine and sebacic acid are monomers obtained from castor oil, and are therefore ideal from the perspective of carbon neutralization. These structural units derived from the diamine having 10 carbon atoms and the structural units derived from the dicarboxylic acid having 10 carbon atoms are in PA1010, and their total is preferably 50% or more of all structural units, more preferably 80% or more, and may also be 100%.
[0058] The polyamide 410 is a polyamide resin having a structure in which a monomer having 4 carbon atoms is copolymerized with a diamine having 10 carbon atoms. Generally, polyamide 410 uses sebacic acid and tetramethylenediamine. As sebacic acid, castor oil, which is a vegetable oil, is preferably used as a raw material from the environmental perspective. As the sebacic acid used here, sebacic acid obtained from castor oil is ideal from the perspective of environmental protection (particularly from the perspective of carbon neutrality).
[0059] The upper limit of the content of the polyamide resin in which at least a part of the raw material is derived from biomass in the biaxially stretched polyamide film or the substrate layer (A layer) of the present invention is 30% by mass, and more preferably 20% by mass. If the content of the polyamide resin in which at least a part of the raw material is derived from biomass exceeds 30% by mass, when the molten film is cast, the molten film becomes unstable and it is difficult to obtain a homogeneous unstretched film.
[0060] [Secondary materials, additives]
[0061] The biaxially stretched polyamide film or the substrate layer (layer A) of the present invention may contain various additives such as other thermoplastic resins, lubricants, heat stabilizers, antioxidants, antistatic agents, antifogging agents, ultraviolet absorbers, dyes, pigments, etc. as needed.
[0062] <Other thermoplastic resins>
[0063] The biaxially stretched polyamide film or substrate layer (layer A) of the present invention may contain a thermoplastic resin in addition to the above-mentioned polyamide 6 and a polyamide resin of which at least a part of the raw material is derived from biomass, within the range not impairing the purpose of the present invention. Examples thereof include polyamide-based resins such as polyamide 12 resin, polyamide 66 resin, polyamide 6 / 12 copolymer resin, polyamide 6 / 66 copolymer resin, and polyamide MXD6 resin.
[0064] If necessary, thermoplastic resins other than polyamide-based resins, for example, polyester-based polymers such as polyethylene terephthalate, polybutylene terephthalate, and poly-2,6-naphthalene dicarboxylate, and polyolefin-based polymers such as polyethylene and polypropylene, may be contained.
[0065] When the raw materials of these thermoplastic resins are derived from biomass, it is preferred because it does not affect the increase or decrease of carbon dioxide on the ground and can reduce the environmental load.
[0066] <Lubricant>
[0067] The biaxially stretched polyamide film or the substrate layer (layer A) of the present invention preferably contains an organic lubricant such as fine particles or fatty acid amide as a lubricant in order to improve the sliding property and facilitate handling.
[0068] The biaxially stretched polyamide film of the present invention has good sliding properties, thereby also having an effect of reducing bag breakage of packaging bags due to friction.
[0069] The fine particles can be appropriately selected from inorganic fine particles such as silica, kaolin, and zeolite, and polymer organic fine particles such as acrylic and polystyrene. Silica fine particles are preferably used from the viewpoint of transparency and slip properties.
[0070] The preferred average particle size of the microparticles is 0.5 to 5.0 μm, more preferably 1.0 to 3.0 μm. If the average particle size is less than 0.5 μm, a large amount of addition is required to obtain good sliding properties. On the other hand, if it exceeds 5.0 μm, there is a tendency that the surface roughness of the film becomes too large and the appearance becomes poor.
[0071] When the silica particles are used, the pore volume of the silica is preferably in the range of 0.5 to 2.0 ml / g, more preferably 0.8 to 1.6 ml / g. If the pore volume is less than 0.5 ml / g, voids are easily generated, which deteriorates the transparency of the film. If the pore volume exceeds 2.0 ml / g, it tends to be difficult to achieve protrusions on the surface due to the particles.
[0072] The biaxially stretched polyamide film or the substrate layer (layer A) of the present invention may contain fatty acid amide and / or fatty acid bisamide for the purpose of improving the sliding property. Examples of the fatty acid amide and / or fatty acid bisamide include erucic acid amide, stearic acid amide, ethylene bisstearic acid amide, ethylene bisbehenic acid amide, and ethylene bisoleic acid amide.
[0073] The content of fatty acid amide and / or fatty acid bisamide in the biaxially stretched polyamide film of the present invention is preferably 0.01 to 0.40 mass %, and more preferably 0.05 to 0.30 mass %. If the content of fatty acid amide and / or fatty acid bisamide is less than the above range, there is a tendency for the slip property to deteriorate. On the other hand, if it exceeds the above range, there is a tendency for the wettability to deteriorate.
[0074] In the biaxially stretched polyamide film or the substrate layer (layer A) of the present invention, a polyamide resin such as polyamide MXD6 resin, polyamide 12 resin, polyamide 66 resin, polyamide 6 / 12 copolymer resin, polyamide 6 / 66 copolymer resin may be added for the purpose of improving the sliding property. Polyamide MXD6 resin is particularly preferred, and it is preferably added in an amount of 1 to 10% by mass.
[0075] <Antioxidants>
[0076] The biaxially stretched polyamide film or the substrate layer (layer A) of the present invention may contain an antioxidant.
[0077] As the antioxidant, a phenolic antioxidant is preferred. The phenolic antioxidant is preferably a completely hindered phenolic compound or a partially hindered phenolic compound. For example, tetrakis-[methylene-3-(3', 5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, stearyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,9-bis[1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane, etc. can be cited.
[0078] By containing the above-mentioned phenolic antioxidant, the film-forming operability of the biaxially stretched polyamide film is improved. In particular, when a recycled film is used as a raw material, there is a tendency that the resin is easily thermally degraded, thereby causing poor film-forming operability and increasing production costs. In contrast, by containing an antioxidant, the thermal degradation of the resin is suppressed and the operability is improved.
[0079] [Surface layer (B layer)]
[0080] As one embodiment of the present invention, a surface layer (B layer) is laminated on at least one surface of a base layer (A layer), so that surface characteristics can be improved.
[0081] The B layer is a layer containing 70% by mass or more of a polyamide 6 resin.
[0082] When the layer B contains 70% by mass or more of the polyamide 6 resin, a biaxially stretched polyamide film having excellent mechanical strength such as impact strength and gas barrier properties against oxygen and the like can be obtained.
[0083] As the polyamide 6 resin, the same polyamide 6 resin as that used in the above-mentioned A layer can be used.
[0084] The layer B may contain various additives such as other thermoplastic resins, lubricants, heat stabilizers, antioxidants, antistatic agents, antifogging agents, ultraviolet absorbers, dyes, pigments, etc., depending on the functions to be imparted to the surface of the layer B.
[0085] When the layer B is used for the outer side of the packaging bag, since friction pinhole resistance is necessary, it is not preferable to contain a soft resin such as a polyamide elastomer or a polyolefin elastomer that generates a large number of voids.
[0086] The B layer may contain a thermoplastic resin other than the above-mentioned polyamide 6 within the range not impairing the purpose of the present invention. Examples thereof include polyamide resins such as polyamide MXD6 resin, polyamide 11 resin, polyamide 12 resin, polyamide 66 resin, polyamide 6 / 12 copolymer resin, and polyamide 6 / 66 copolymer resin.
[0087] If necessary, the thermoplastic resin other than the polyamide resin may be contained, for example, polyester polymers such as polyethylene terephthalate, polybutylene terephthalate, and poly-2,6-naphthalene dicarboxylate, and polyolefin polymers such as polyethylene and polypropylene.
[0088] In order to improve the slidability of the film, the layer B preferably contains fine particles, an organic lubricant or the like as a lubricant.
[0089] By improving the sliding property, the handling property of the film is improved, and the breakage of the packaging bag due to friction is reduced.
[0090] The fine particles can be appropriately selected from inorganic fine particles such as silica, kaolin, and zeolite, and polymer organic fine particles such as acrylic and polystyrene. Silica fine particles are preferably used from the viewpoint of transparency and slip properties.
[0091] The preferred average particle size of the microparticles is 0.5 to 5.0 μm, more preferably 1.0 to 3.0 μm. If the average particle size is less than 0.5 μm, a large amount of addition is required to obtain good sliding properties. On the other hand, if it exceeds 5.0 μm, there is a tendency that the surface roughness of the film becomes too large and the appearance becomes poor.
[0092] When the above-mentioned silica particles are used, the pore volume of the silica is preferably in the range of 0.5 to 2.0 ml / g, and more preferably in the range of 0.8 to 1.6 ml / g. If the pore volume is less than 0.5 ml / g, voids are easily generated, which deteriorates the transparency of the film. If the pore volume exceeds 2.0 ml / g, there is a tendency that surface protrusions caused by the particles are difficult to achieve.
[0093] The organic lubricant may contain fatty acid amide and / or fatty acid bisamide. Examples of the fatty acid amide and / or fatty acid bisamide include erucic acid amide, stearic acid amide, ethylene bisstearic acid amide, ethylene bisbehenic acid amide, and ethylene bisoleic acid amide.
[0094] The content of fatty acid amide and / or fatty acid bisamide added to layer B is preferably 0.01 to 0.40 mass %, and more preferably 0.05 to 0.30 mass %. If the content of fatty acid amide and / or fatty acid bisamide is less than the above range, there is a tendency for the sliding property to deteriorate. On the other hand, if it exceeds the above range, there is a tendency for the wettability to deteriorate.
[0095] In the B layer, in order to improve the slippage of the film, a polyamide resin other than polyamide 6, such as polyamide MXD6 resin, polyamide 11, polyamide 12 resin, polyamide 66 resin, polyamide 6 / 12 copolymer resin, polyamide 6 / 66 copolymer resin, etc., can be added. Polyamide MXD6 resin is particularly preferred, and 1 to 10% by mass is preferably added. If it is less than 1% by mass, the effect of improving the slippage of the film is small. In the case of more than 10% by mass, the effect of improving the slippage of the film is saturated.
[0096] Polyamide MXD6 resin is produced by the polycondensation of m-xylylenediamine and adipic acid.
[0097] The relative viscosity of polyamide MXD6 is preferably 1.8 to 4.5, more preferably 2.0 to 3.2. When the relative viscosity is less than 1.8 or greater than 4.5, kneading with the polyamide resin may be difficult in an extruder.
[0098] When fine particles, an organic lubricant, or a polyamide resin such as a polyamide MXD6 resin is added to the B layer for the purpose of improving the slip properties of the film, it is preferred to reduce the amount of these added to the base layer (A layer) because a film with excellent transparency and slip properties can be obtained.
[0099] In order to improve the adhesiveness, a polyamide resin other than polyamide 6 may be added to layer B. In this case, copolymerized polyamide resins such as polyamide 6 / 12 copolymerized resin and polyamide 6 / 66 copolymerized resin are preferred.
[0100] The layer B of the biaxially stretched polyamide film of the present invention may contain an antioxidant similarly to the layer A described above.
[0101] As a method of adding secondary materials and additives such as lubricants and antioxidants to the biaxially stretched polyamide film or the substrate layer (A layer) and the surface layer (B layer) of the present invention, they can be added during the polymerization of the resin or during melt extrusion using an extruder. It is also possible to prepare a high-concentration masterbatch and add the masterbatch to the polyamide resin during film production. This can be done by such a known method.
[0102] [Biaxially stretched polyamide film]
[0103] The thickness of the biaxially stretched polyamide film of the present invention is not particularly limited, but when used as a packaging material, it is usually 100 μm or less, and a film with a thickness of 5 to 50 μm is generally used, and a film with a thickness of 8 to 30 μm is particularly used.
[0104] In the thickness composition of each layer of the biaxially stretched polyamide film of the present invention, when the thickness of the B layer accounts for most of the total thickness of the film, the bending pinhole resistance is reduced. Therefore, in the present invention, it is preferred that the thickness of the A layer is set to 50 to 93% of the total thickness of the A layer and the B layer, and particularly 70 to 93%.
[0105] Regarding the biaxially stretched polyamide film of the present invention, the number of pinhole defects when a torsion bending test using a Gelbo twist tester at a temperature of 1° C. is performed 1000 times based on the measurement method described in the Examples is 10 or less. More preferably, it is 5 or less. The smaller the number of pinhole defects after the bending test, the better the bending pinhole resistance. If the number of pinholes is 10 or less, a packaging bag that is unlikely to generate pinholes even when a load is applied to the packaging bag during transportation, etc. can be obtained.
[0106] In addition, the distance until pinholes are generated in the friction pinhole resistance test of the biaxially stretched polyamide film of the present invention is 2900 cm or more. It is more preferably 3100 cm or more, and further preferably 3300 cm or more. The longer the distance until pinholes are generated, the better the friction pinhole resistance is. If the distance until pinholes are generated is 2900 cm or more, a packaging bag that is unlikely to generate pinholes even if the packaging bag rubs against a corrugated carton during transportation can be obtained.
[0107] The biaxially stretched polyamide film of the present invention is characterized by being excellent in both the above-mentioned bending pinhole resistance and friction pinhole resistance. The biaxially stretched polyamide film of the present invention having these characteristics is unlikely to generate pinholes during transportation and is therefore extremely useful as a packaging film.
[0108] The film of the present invention has a heat shrinkage rate of 0.6 to 3.0% in both the machine direction (hereinafter referred to as MD direction) and the width direction (hereinafter referred to as TD direction) at 160°C for 10 minutes, preferably 0.6 to 2.5%. When the heat shrinkage rate exceeds 3.0%, curling and shrinkage may occur when heat is applied in subsequent processes such as lamination and printing. In addition, there is a situation where the lamination strength with the sealing film is weakened. Although the heat shrinkage rate can be less than 0.6%, there is a situation where it becomes mechanically brittle. In addition, productivity deteriorates, so it is not preferred.
[0109] Excellent impact resistance is a characteristic of biaxially stretched polyamide films, and thus the impact strength of the biaxially stretched polyamide film of the present invention is preferably 0.7 J / 15 μm or more, and more preferably 0.9 J / 15 μm or more.
[0110] The haze value of the biaxially stretched polyamide film of the present invention is preferably 10% or less, more preferably 7% or less, and even more preferably 5% or less.
[0111] When the haze value is small, transparency and glossiness are good, so when used for packaging bags, beautiful printing can be achieved, thereby improving the product value.
[0112] If fine particles are added to improve the slip properties of the film, the haze value increases. Therefore, the haze value can be reduced by adding fine particles only to the layer B of the surface layer.
[0113] The biaxially stretched polyamide film of the present invention is preferably prepared by radiocarbon (C 14 ) The content of carbon derived from biomass (also referred to as biomass degree) measured contains 1 to 15% relative to the total carbon in the polyamide membrane.
[0114] It is known that atmospheric carbon dioxide contains C in a fixed proportion (105.5 pMC). 14 , thus absorbing carbon dioxide from the atmosphere and growing plants, such as C in grains 14 The content is also about 105.5 pMC. In addition, it is known that fossil fuels contain almost no C 14 Therefore, by measuring the C contained in all carbon atoms in polyamide 14 The proportion of carbon derived from biomass can be calculated by measuring the proportion of carbon derived from biomass.
[0115] The lamination strength of the biaxially stretched polyamide film of the present invention and the polyethylene-based sealant described in Examples after bonding together is 4.0 N / 15 mm or more.
[0116] The biaxially stretched polyamide film is usually laminated with a sealing film to form a packaging bag. If the lamination strength is 4.0 N / 15 mm or more, when the biaxially stretched polyamide film of the present invention is used to make packaging bags in various laminated structures, the strength of the sealing portion can be sufficiently obtained, and a strong packaging bag that is difficult to break can be obtained.
[0117] In order to adjust the lamination strength to 4.0 N / 15 mm or more, the biaxially stretched polyamide film of the present invention may be subjected to corona treatment, coating treatment, flame treatment or the like.
[0118] [Method for producing film]
[0119] The biaxially stretched polyamide film of the present invention can be produced by a known production method.
[0120] For example, the method includes a sequential biaxial stretching method and a simultaneous biaxial stretching method. The sequential biaxial stretching method is preferred because it can increase the film forming speed and is advantageous in terms of production cost.
[0121] The method for producing the biaxially stretched polyamide film of the present invention will be described.
[0122] First, a raw material resin is melt-extruded using an extruder, extruded from a T-die into a film shape, and cast on a cooling roll to be cooled to obtain an unstretched film.
[0123] When a biaxially stretched polyamide film is produced in which a surface layer (B layer) is laminated on at least one side of a substrate layer (A layer), a coextrusion method using a feed block, a multi-manifold, or the like is preferably used to obtain an unstretched film in which the A layer and the B layer are laminated. In addition to the coextrusion method, a dry lamination method, an extrusion lamination method, or the like may also be used.
[0124] When lamination is performed by a coextrusion method, it is desirable that the difference in melt viscosity between the polyamide resin compositions used in the A layer and the B layer be reduced.
[0125] The melting temperature of the resin is preferably 220 to 350° C. If it is less than 220° C., unmelted materials may be produced, and defects such as defects may occur. If it exceeds 350° C., degradation of the resin may be observed, and a decrease in molecular weight and a decrease in appearance may occur. The mold temperature is preferably 250 to 350° C.
[0126] The cooling roll temperature is preferably -30 to 80°C, more preferably 0 to 50°C.
[0127] In order to cast the film-like melt extruded from the T-die onto a rotating cooling drum and cool it to obtain an unstretched film, for example, a method using an air knife or an electrostatic contact method of applying an electrostatic charge can be preferably used. The latter is particularly preferably used.
[0128] In addition, it is preferred that the surface of the cast unstretched film opposite to the cooling roll is also cooled. For example, the surface of the unstretched film opposite to the cooling roll is preferably subjected to the following methods: a method of contacting the surface with a cooling liquid in a tank, a method of applying liquid evaporated by a spray nozzle, a method of cooling by blowing a high-speed fluid, etc. The unstretched film thus obtained is stretched in biaxial directions to obtain the biaxially stretched polyamide film of the present invention.
[0129] The stretching method may be a simultaneous biaxial stretching method or a sequential biaxial stretching method.
[0130] In any case, as the stretching method in the MD direction, one-stage stretching or multi-stage stretching such as two-stage stretching can be used. As described later, in terms of physical properties and physical property uniformity (isotropy) in the MD direction and the TD direction, multi-stage stretching in the MD direction such as two-stage stretching is preferred rather than one-stage stretching.
[0131] The stretching in the MD direction in the sequential biaxial stretching method is preferably roll stretching.
[0132] The lower limit of the stretching temperature in the MD direction is preferably 50° C., more preferably 55° C., and further preferably 60° C. If the temperature is lower than 50° C., the resin may not soften and thus may be difficult to stretch.
[0133] The upper limit of the stretching temperature in the MD direction is preferably 120° C., more preferably 115° C., and further preferably 110° C. If the temperature exceeds 120° C., the resin may become too soft and stable stretching may not be achieved.
[0134] The lower limit of the stretching ratio in the MD direction (when stretching is performed in multiple stages, the total stretching ratio obtained by multiplying each ratio) is preferably 2.2 times, more preferably 2.5 times, and further preferably 2.8 times. If it is less than 2.2 times, not only the thickness accuracy in the MD direction is reduced, but also the crystallinity sometimes becomes too low and the impact strength is reduced.
[0135] The upper limit of the stretch ratio in the MD direction is preferably 5.0 times, more preferably 4.5 times, and most preferably 4.0 times. If it exceeds 5.0 times, subsequent stretching may become difficult.
[0136] In addition, when the stretching in the MD direction is performed in multiple stages, the above-mentioned stretching can be performed in each stage of stretching, but the stretching ratio needs to be adjusted so that the product of the total stretching ratio in the MD direction becomes 5.0 or less. For example, in the case of two-stage stretching, it is preferred that the stretching in the first stage is 1.5 to 2.1 times, and the stretching in the second stage is 1.5 to 1.8 times.
[0137] The film stretched in the MD direction is stretched in the TD direction by a tenter, heat-fixed, and subjected to a relaxation treatment (also referred to as a relaxation treatment).
[0138] The lower limit of the stretching temperature in the TD direction is preferably 50° C., more preferably 55° C., and further preferably 60° C. If the temperature is lower than 50° C., the resin may not soften and thus may be difficult to stretch.
[0139] The upper limit of the stretching temperature in the TD direction is preferably 190° C., more preferably 185° C., and further preferably 180° C. If it exceeds 190° C., crystallization may occur, making stretching difficult.
[0140] The lower limit of the stretching ratio in the TD direction (when stretching is performed in multiple stages, the total stretching ratio obtained by multiplying each ratio) is preferably 2.8, more preferably 3.2, further preferably 3.5, and particularly preferably 3.8. If it is less than 2.8, not only the thickness accuracy in the TD direction is reduced, but also the crystallinity sometimes becomes too low and the impact strength is reduced.
[0141] The upper limit of the draw ratio in the TD direction is preferably 5.5 times, more preferably 5.0 times, further preferably 4.7, particularly preferably 4.5, and most preferably 4.3 times. If it exceeds 5.5 times, the productivity may sometimes be significantly reduced.
[0142] The selection of the heat setting temperature is an important factor in the present invention. As the heat setting temperature increases, the crystallization and orientation of the film proceed gently, the impact strength can be improved, and the heat shrinkage rate can be reduced. On the other hand, when the heat setting temperature is low, the crystallization and orientation are not sufficiently relaxed, and the heat shrinkage rate cannot be sufficiently reduced. In addition, if the heat setting temperature becomes too high, the deterioration of the resin progresses, and the toughness of the film such as the impact strength is rapidly lost.
[0143] The lower limit of the heat setting temperature is preferably 210 °C, more preferably 212 °C. If the heat setting temperature is low, there is a tendency that the heat shrinkage rate becomes too large, resulting in a decrease in the appearance after lamination and a decrease in the lamination strength.
[0144] The upper limit of the heat setting temperature is preferably 220 °C, more preferably 218 °C. If the heat setting temperature is too high, there is a tendency that the impact strength decreases.
[0145] The heat setting time is preferably 0.5 to 20 seconds. Further, it is 1 to 15 seconds. The heat setting time can be set to an appropriate time by balancing with the heat setting temperature and the wind speed in the heat setting area. If the heat setting conditions are too weak, the crystallization and orientation relaxation become insufficient, causing the above problems. If the heat setting conditions are too strong, the film toughness decreases.
[0146] The method of performing a relaxation treatment after the heat setting treatment is effective for controlling the heat shrinkage rate. The temperature for the relaxation treatment can be selected within the range from the heat setting treatment temperature to the glass transition temperature (Tg) of the resin, but preferably it is from the heat setting treatment temperature - 10 °C to Tg + 10 °C. If the relaxation temperature is too high, the shrinkage speed is too fast, which may cause strain and the like, so it is not preferred. On the contrary, if the relaxation temperature is too low, it cannot be a relaxation treatment, but only sags (in Japanese: 弛む), and the heat shrinkage rate does not decrease, and the dimensional stability deteriorates.
[0147] The lower limit of the relaxation rate of the relaxation treatment is preferably 0.5%, more preferably 1%. If it is less than 0.5%, sometimes the heat shrinkage rate will not sufficiently decrease.
[0148] The upper limit of the relaxation rate is preferably 20%, more preferably 15%, further preferably 10%. If it exceeds 20%, sagging occurs in the tenter, and sometimes production becomes difficult.
[0149] In addition, regarding the biaxially stretched polyamide film of the present invention, in order to make the dimensional stability good according to the purpose, heat treatment and humidity control treatment may also be implemented. In addition, in order to make the adhesion of the film surface good, corona treatment, coating treatment, flame treatment, etc. may also be implemented, or printing processing, metal objects, inorganic oxides, etc. may be evaporated. It should be noted that as the evaporated film formed by the evaporation process, the evaporated film of aluminum, silicon oxide, aluminum oxide alone or a mixture may be suitably used. In addition, by applying a protective layer on these evaporated films, the barrier properties for oxygen and hydrogen may be improved.
[0150] The biaxially stretched polyamide film of the present invention is processed into a packaging bag after being formed into a laminated film laminated with a sealant film and the like.
[0151] Examples of the sealant film include an unstretched linear low-density polyethylene film, an unstretched polypropylene film, and an ethylene-vinyl alcohol copolymer resin film.
[0152] The layer constitution of the laminated film of the present invention using the biaxially stretched polyamide film of the present invention is not particularly limited as long as the laminated film has the biaxially stretched polyamide film of the present invention. In addition, the film used in the laminated film may be a raw material derived from petrochemicals or a raw material derived from biomass, but from the viewpoint of reducing the environmental load, polylactic acid, polyethylene terephthalate, polybutylene succinate, polyethylene, polyethylene furandicarboxylate, etc. obtained by polymerization of raw materials derived from biomass are preferably used.
[0153] As examples of the layer constitution of the laminated film of the present invention, when the boundary of the layer is represented by “ / ”, for example, ONY / contact / LLDPE, ONY / contact / CPP, ONY / contact / Al / contact / CPP, ONY / contact / Al / contact / LLDPE, ONY / PE / Al / contact / LLDPE, ONY / contact / Al / PE / LLDPE, PET / contact / ONY / contact / LLDPE, PET / contact / ONY / PE / LLDPE, PET / contact / ONY / PE / LLDPE, PET / contact / ONY / contact / A l / connection / LLDPE, PET / connection / Al / connection / ONY / connection / LLDPE, PET / connection / Al / connection / ONY / PE / LLDPE, PET / PE / Al / PE / ONY / PE / LLDPE, PET / connection / ONY / connection / CPP, PET / connection / ONY / connection / Al / connection / CPP, PET / connection / Al / connection / ONY / connection / CPP, ONY / connection / PET / connection / LLDPE, ONY / connection / PET / PE / LLDPE, ONY / connection / PET / connection / CPP, ONY / / Al / / PET / / LLDPE, ONY / connection / Al / connection / PET / PE / LLDPE, ONY / PE / LLDPE, ONY / PE / CPP, ONY / PE / Al / PE, ONY / PE / Al / PE / LLDPE, OPP / connection / ONY / connection / LLDPE, ONY / connection / EVOH / connection / LLDPE, ONY / connection / EVOH / connection / CPP, ONY / connection / Aluminum steam Plated PET / joint / LLDPE, ONY / joint / aluminum vapor-deposited PET / joint / ONY / joint / LLDPE, ONY / joint / aluminum vapor-deposited PET / PE / LLDPE, ONY / PE / aluminum vapor-deposited PET / PE / LLDPE, ONY / joint / aluminum vapor-deposited PET / joint / CPP, PET / joint / aluminum vapor-deposited PET / joint / ONY / joint / LLDPE, CPP / joint / ONY / joint / LLDPE, ONY / joint / aluminum vapor-deposited LLDPE, ONY / joint / aluminum vapor-deposited CPP, etc.
[0154] In addition, each abbreviation used for the said layer structure is as follows.
[0155] ONY: biaxially stretched polyamide film of the present invention, PET: stretched polyethylene terephthalate film, LLDPE: unstretched linear low-density polyethylene film, CPP: unstretched polypropylene film, OPP: stretched polypropylene film, PE: extrusion laminated or unstretched low-density polyethylene film, Al: aluminum foil, EVOH: ethylene-vinyl alcohol copolymer resin, bond: adhesive layer for bonding films to each other, aluminum vapor deposition means that aluminum is vapor-deposited.
[0156] Example
[0157] Next, the present invention is further described in detail by examples, but the present invention is not limited to the following examples. It should be noted that the film evaluation was performed by the following measurement method. Unless otherwise specified, the measurement was performed in a measurement room in an environment of 23° C. and a relative humidity of 65%.
[0158] (1) Haze value of film
[0159] The haze was measured using a direct-reading haze meter manufactured by Toyo Seiki Seisaku-sho, Ltd. in accordance with JIS-K-7105.
[0160] (2) Film thickness
[0161] The film was divided into 10 equal parts along the TD direction (for narrow films, the width was divided into equal parts to ensure the width that can measure the thickness), and 10 films with a length of 100 mm along the MD direction were overlapped and cut out, and conditioned for more than 2 hours in an environment with a temperature of 23°C and a relative humidity of 65%. The thickness of the center of each sample was measured with a thickness gauge made by TESTER Industries, and the average value was taken as the thickness.
[0162] (3) Biomass of membrane
[0163] The biomass of the obtained membrane was determined by radiocarbon (C 14 ) measurement to be carried out.
[0164] (4) Thermal shrinkage of the film
[0165] The heat shrinkage ratio was measured as follows in accordance with the dimensional change test method described in JIS C2318 except that the test temperature was 160° C. and the heating time was 10 minutes.
[0166] Thermal shrinkage = [(length before treatment - length after treatment) / length before treatment] × 100 (%)
[0167] (5) Impact strength of film
[0168] The measurement was performed using a film impact tester manufactured by Toyo Seiki Seisaku-sho, Ltd. The measured value was converted per 15 μm thickness and represented by J (joule) / 15 μm.
[0169] (6) Dynamic friction coefficient of the film
[0170] The dynamic friction coefficient between the outer surfaces of the film roll was evaluated under the following conditions in accordance with JIS-C2151: The test piece had a size of 130 mm in width and 250 mm in length and the test speed was 150 mm / min.
[0171] (7) Film resistance to bending pinholes
[0172] The number of bending fatigue pinholes was measured by the following method using a Gelbo twist tester manufactured by Rigaku Kogyo Co., Ltd.
[0173] After applying the polyester adhesive to the film prepared in the example, a linear low-density polyethylene film (L-LDPE film: manufactured by Toyobo Co., Ltd., L4102) with a thickness of 40 μm was dry-laminated and aged for 3 days at 40°C to form a laminated film. The obtained laminated film was cut into 12 inches × 8 inches and made into a cylindrical shape with a diameter of 3.5 inches. One end of the cylindrical film was fixed to the fixed head side of the Gelbo twist tester, and the other end was fixed to the movable head side, and the initial clamping interval was set to 7 inches. The bending fatigue was performed 1000 times at a speed of 40 times / minute, and the number of pinholes generated by the laminated film was counted. The bending fatigue was: a 440-degree twist was given in the first 3.5 inches of the stroke (Japanese: ストローク), and then 2.5 inches were used to end the entire stroke with a straight horizontal movement. It should be noted that the measurement was performed at 1°C. The L-LDPE film side of the test film was placed on filter paper (ADVANTEC, No. 50) with the lower surface, and the four corners were fixed with Cellotape (registered trademark). Ink (PILOT ink (product number INK-350-blue) diluted 5 times with pure water) was applied to the test film and spread on one side using a rubber roller. After wiping off unnecessary ink, the test film was removed and the number of dots of ink attached to the filter paper was measured.
[0174] (8) Friction pinhole resistance of the film
[0175] A friction test was performed using a fastness tester (Toyo Seiki Seisaku-sho, Ltd.) by the following method to measure the pinhole generation distance.
[0176] The same laminated film as that prepared in the above-mentioned evaluation of pinhole resistance to bending was folded in two to prepare a test sample with sharp corners, and the inner surface of the corrugated paper was rubbed with an amplitude of 25 cm, an amplitude speed of 30 times / minute, and a weight of 100 g using a fastness tester. The corrugated paper used was K280×P180×K210 (AF) = (surface material liner×core material×back material liner (type of corrugated paper).
[0177] The pinhole generation distance is calculated according to the following procedure. The longer the pinhole generation distance is, the better the friction pinhole resistance is.
[0178] First, a friction test is performed with an amplitude of 100 times and a distance of 2500cm. In the case where no pinholes are generated, the friction test is performed by increasing the amplitude by 20 times and a distance of 500cm. In addition, in the case where no pinholes are generated, the friction test is performed by further increasing the amplitude by 20 times and a distance of 500cm. Repeat this operation, and mark the distance where pinholes are generated with × to set it as level 1. In the case where a pinhole is generated with an amplitude of 100 times and a distance of 2500cm, the friction test is performed by reducing the amplitude by 20 times and a distance of 500cm. In addition, in the case where a pinhole is generated, the friction test is performed by further reducing the amplitude by 20 times and a distance of 500cm. Repeat this operation, and mark the distance where no pinholes are generated with ○ to set it as level 1.
[0179] Next, as level 2, if the last result in level 1 is ○, the friction test is performed by increasing the amplitude by 20 times, and if no pinhole is generated, ○ is marked, and if a pinhole is generated, × is marked. If the last result in level 1 is ×, the friction test is performed by decreasing the amplitude by 20 times, and if no pinhole is generated, ○ is marked, and if a pinhole is generated, × is marked.
[0180] In addition, as levels 3 to 20, if the previous level was ○, the friction test was performed by increasing the amplitude by 20 times, and if no pinhole was generated, ○ was marked, and if a pinhole was generated, × was marked. If the previous level was ×, the friction test was performed by reducing the amplitude by 20 times, and if no pinhole was generated, ○ was marked, and if a pinhole was generated, × was marked. Repeat this operation to mark ○ or × for levels 3 to 20.
[0181] For example, the results shown in Table 1 are obtained. Table 1 is used as an example to illustrate the method for obtaining the pinhole generation distance.
[0182] The number of trials with ○ and × at each distance was counted.
[0183] The distance with the most tests is set as the central value, and the coefficient is set to 0. When the distance is longer than the central value, the coefficient is set to +1, +2, +3, etc. every 500 cm, and when the distance is shorter than the central value, the coefficient is set to -1, -2, -3, etc. every 500 cm.
[0184] In all tests from level 1 to level 20, the number of tests in which no holes were generated was compared with the number of tests in which holes were generated, and for the following cases A and B, the friction pinhole generation distance was calculated using various formulas.
[0185] A: In all the tests, the number of tests without holes is greater than or equal to the number of tests with holes.
[0186] Friction pinhole generation distance = median value + 500 × (Σ (coefficient × number of tests without pinhole generation) / number of tests without pinhole generation) + 1 / 2)
[0187] B: In all the tests, the number of tests without holes is less than the number of tests with holes.
[0188] Friction pinhole generation distance = median value + 500 × (Σ (coefficient × number of tests where pinholes were generated) / number of tests where pinholes were generated) - 1 / 2)
[0189] [Table 1]
[0190]
[0191] (9) Lamination strength with polyethylene sealing materials
[0192] A laminated film produced by the same operation as the method described in the description of the evaluation of bending pinhole resistance was cut into strips of 15 mm in width × 200 mm in length, and one end of the laminated film was peeled off at the interface between the biaxially stretched polyamide film and the linear low-density polyethylene film. The lamination strength was measured three times in the MD direction and TD direction respectively using (manufactured by Shimadzu Corporation, AUTOGRAPH) under the conditions of temperature 23°C, relative humidity 50%, stretching speed 200 mm / min, and peeling angle 90°, and the average value was used for evaluation.
[0193] (10) Film stability during casting
[0194] The film forming stability was evaluated as follows by visually observing the process of extruding the molten resin from a T-die into a film shape, casting on a cooling roll, and cooling to obtain an unstretched film.
[0195] ○: Film formation was stable and a homogeneous unstretched film was obtained.
[0196] △: Film formation was slightly unstable, and fluctuations in the width of the unstretched film were observed, but biaxial stretching was possible.
[0197] ×: Film formation was unstable and the unstretched film was not homogeneous, so a biaxially stretched film could not be obtained.
[0198] (11) Generation cycle of thermal degradation products generated at the die lip exit
[0199] After cleaning the die lip, film production was started, and the time until thermally degraded products were generated on the die lip was observed.
[0200] (12) Relative viscosity of raw material polyamide
[0201] 0.25 g of polyamide was dissolved in 96% sulfuric acid in a 25 ml volumetric flask to a concentration of 1.0 g / dl, and the relative viscosity of the obtained polyamide solution was measured at 20°C.
[0202] (13) Melting point of raw material polyamide
[0203] The melting point was determined using a Seiko Instruments SSC5200 differential scanning calorimeter in accordance with JIS K7121 in a nitrogen atmosphere with a sample weight of 10 mg, a heating start temperature of 30° C., and a heating rate of 20° C. / min. The endothermic peak temperature (Tmp) was determined.
[0204] (Example 1-1)
[0205] The following molten resin composition was extruded from the T-film into a film using an apparatus including an extruder and a 380 mm wide T-film, and cast on a cooling roll regulated at 20° C. for electrostatic adhesion to obtain an unstretched film having a thickness of 200 μm.
[0206] Resin composition: A resin composition containing 97 parts by mass of polyamide 6 (manufactured by Toyobo Co., Ltd., relative viscosity 2.8, melting point 220°C), 3.0 parts by mass of polyamide 11 (manufactured by Arkema, relative viscosity 2.5, melting point 186°C), 0.45 parts by mass of porous silica fine particles (manufactured by Fuji Silysia Chemical Co., Ltd., average particle size 2.0 μm, pore volume 1.6 ml / g), and 0.15 parts by mass of fatty acid bisamide (manufactured by Kyoeisha Chemical Co., Ltd., ethylene bisstearamide).
[0207] The obtained unstretched film was introduced into a roll stretching machine, and stretched 1.73 times in the MD direction at 80°C by using the circumferential speed difference of the rolls, and then further stretched 1.85 times at 70°C. Subsequently, the uniaxially stretched film was continuously introduced into a tenter-type stretching machine, preheated at 110°C, stretched 1.2 times in the TD direction at 120°C, stretched 1.7 times at 130°C, stretched 2.0 times at 160°C, heat-set at 218°C, and then 7% relaxation treatment was performed at 218°C, and then the surface on the side to be dry-laminated with the linear low-density polyethylene film was corona-discharged to obtain a biaxially stretched polyamide film. The evaluation results of the obtained biaxially stretched film are shown in Table 2.
[0208] (Examples 1-2 to 1-9 and Comparative Examples 1-1 to 1-5)
[0209] A biaxially stretched film was obtained in the same manner as in Example 1 except that the film-forming conditions such as the raw material resin composition and the heat setting temperature were changed as shown in Table 2. Table 2 shows the evaluation results of the obtained biaxially stretched film.
[0210] In addition, as polyamide 410, polyamide 610, and polyamide 1010 which are polyamide resins containing a raw material at least partly derived from biomass, the following polyamides were used, respectively.
[0211] Polyamide 410: (manufactured by DSM, ECOPaXX Q150-E, melting point 250°C)
[0212] Polyamide 610: (RilsanS SMNO, manufactured by Arkema, melting point 222°C)
[0213] Polyamide 1010: (RilsanT TMNO, manufactured by Arkema, melting point 202°C)
[0214] However, in Comparative Example 1-4, the molten resin could not be stably extruded from the T-die into a film shape, and a homogeneous unstretched film was not obtained, so biaxial stretching could not be performed.
[0215]
[0216] As shown in Table 2, the films of the Examples were excellent in both bending pinhole resistance and friction pinhole resistance. In addition, the haze was low, the transparency was good, the impact strength was strong, and the lamination strength with the sealing film was high, which was excellent as a packaging film.
[0217] The biaxially stretched polyamide films of Comparative Examples 1-1 and 1-2 that did not contain a material for improving the bending pinhole resistance and the biaxially stretched polyamide film of Comparative Example 1-3 that had an excessively low content of polyamide 11 had poor bending pinhole resistance.
[0218] In Comparative Example 1-4, since the content of polyamide 11 was too high, the molten resin could not be stably extruded from the T-film into a film shape, a homogeneous unstretched film could not be obtained, and a biaxially stretched polyamide film could not be obtained.
[0219] In Comparative Examples 1-5, polyamide elastomers that were previously used as materials for improving bending pinhole resistance were used. As a result, although the bending pinhole resistance was good, the friction pinhole resistance was poor. In addition, deteriorated products were easily attached to the mold during long-term production, and there was a disadvantage that long-term continuous production could not be achieved.
[0220] (Example 2-1)
[0221] Using an apparatus comprising two extruders and a 380 mm wide co-extrusion T-die, the molten resin was extruded into a film from the T-film by stacking in a B layer / A layer / B layer configuration using a feed head method, and cast on a cooling roll regulated at 20°C for electrostatic adhesion to obtain an unstretched film with a thickness of 200 μm.
[0222] The resin compositions of the A layer and the B layer are as follows.
[0223] The resin composition constituting the A layer is a polyamide resin composition containing 97 parts by mass of polyamide 6 (manufactured by Toyobo Co., Ltd., relative viscosity 2.8, melting point 220° C.) and 3.0 parts by mass of polyamide 11 (manufactured by Chisei Co., Ltd., relative viscosity 2.5, melting point 186° C.).
[0224] The resin composition constituting the B layer: a resin composition containing 95 parts by mass of polyamide 6 (manufactured by Toyobo Co., Ltd., relative viscosity 2.8, melting point 220°C), 5.0 parts by mass of polyamide MXD6 (manufactured by Mitsubishi Gas Chemical Co., Ltd., relative viscosity 2.1, melting point 237°C), 0.54 parts by mass of porous silica fine particles (manufactured by FUJI SILYSIA CHEMICAL Co., Ltd., average particle size 2.0 μm, pore volume 1.6 ml / g), and 0.15 parts by mass of fatty acid bisamide (ethylene bisstearamide manufactured by Kyoeisha Chemical Co., Ltd.).
[0225] The configuration of the feed head and the discharge rate of the extruder were adjusted so that the total thickness of the biaxially stretched polyamide film was 15 μm, the thickness of the base layer (layer A) was 12 μm, and the thickness of the surface layers (layer B) on both the front and back sides were each 1.5 μm.
[0226] The obtained unstretched film was introduced into a roll stretching machine, and stretched 1.73 times in the MD direction at 80°C by using the circumferential speed difference of the rolls, and then further stretched 1.85 times at 70°C. Next, the uniaxially stretched film was continuously introduced into a tenter-type stretching machine, preheated at 110°C, stretched 1.2 times in the TD direction at 120°C, stretched 1.7 times at 130°C, stretched 2.0 times at 160°C, heat-set at 218°C, and then 7% relaxation treatment was performed at 218°C, and then the surface on the side to be dry-laminated with the linear low-density polyethylene film was corona-discharged to obtain a biaxially stretched polyamide film. The evaluation results of the obtained biaxially stretched film are shown in Table 2.
[0227] (Examples 2-2 to 2-11 and Comparative Examples 2-1 to 2-7)
[0228] A biaxially stretched film was obtained in the same manner as in Example 2-1 except that the film forming conditions such as the resin composition of the A layer and the B layer and the heat setting temperature were changed as shown in Tables 3 and 4. The evaluation results of the obtained biaxially stretched film are shown in Tables 3 and 4.
[0229] However, in Comparative Example 2-4, the molten resin could not be stably extruded from the T-die into a film shape, and a homogeneous unstretched film was not obtained, so biaxial stretching could not be performed.
[0230] [Table 3]
[0231]
[0232] [Table 4]
[0233]
[0234] As shown in Table 3 and Table 4, the films of the examples obtained films with both good flexing pinhole resistance and rubbing pinhole resistance. In addition, they had low haze, good transparency, high impact strength, and high lamination strength with the sealing film, and were excellent as packaging films.
[0235] For the biaxially stretched polyamide films of Comparative Examples 2-1 and 2-2 that did not contain the material for improving flexing pinhole resistance and the biaxially stretched polyamide film of Comparative Example 2-3 with too little polyamide 11 content, the flexing pinhole resistance was poor.
[0236] In Comparative Example 2-4, due to too much polyamide 11 content, the molten resin could not be stably extruded into a film shape from the T die, and a homogeneous unstretched film was not obtained, and a biaxially stretched polyamide film was not obtained.
[0237] In Comparative Example 2-5, due to the small thickness and thickness ratio of the A layer, the flexing pinhole resistance of the film was poor.
[0238] In Comparative Example 2-6, due to a large amount of polyamide MXD6 and a small amount of polyamide 6 resin in the B layer, the flexing pinhole resistance and rubbing pinhole resistance of the film were poor.
[0239] Comparative Example 2-7 used a polyamide elastomer that was conventionally used as a material for improving flexing pinhole resistance. As a result, although the flexing pinhole resistance was good, the rubbing pinhole resistance was poor. In addition, during long-term production, deteriorated products were likely to adhere to the mold, and there was a drawback that long-term continuous production could not be achieved.
[0240] [Examples 1-10, Examples 2-12]
[0241] The following laminates (1) to (9) were produced using the biaxially stretched polyamide films produced in Examples 1-2 and Examples 2-2, and three-side sealed type and pillow type packaging bags were produced using the laminates (1) to (9). Packaging bags with good appearance and difficult to break in the drop impact test could be produced.
[0242] (1) Biaxially stretched polyamide film layer / Printing layer / Polyurethane-based adhesive layer / Linear low-density polyethylene film sealing layer (Japanese: シーラント層).
[0243] (2) Biaxially stretched polyamide film layer / Printing layer / Polyurethane-based adhesive layer / Unstretched polypropylene film sealing layer.
[0244] (3) Biaxially oriented PET film layer / printing layer / polyurethane-based adhesive layer / biaxially oriented polyamide film layer / polyurethane-based adhesive layer / unstretched polypropylene film sealing layer.
[0245] (4) Biaxially oriented PET film layer / printing layer / polyurethane-based adhesive layer / biaxially oriented polyamide film layer / polyurethane-based adhesive layer / linear low density polyethylene film sealing layer.
[0246] (5) Biaxially oriented polyamide film layer / anchor coating layer (Japanese: アンカーコート層) / inorganic thin film layer / inorganic thin film protective layer / printing layer / polyurethane-based adhesive layer / linear low density polyethylene film sealing layer.
[0247] (6) Linear low density polyethylene film sealing layer / polyurethane-based adhesive layer / biaxially oriented polyamide film layer / anchor coating layer / inorganic thin film layer / polyurethane-based adhesive layer / linear low density polyethylene film sealing layer.
[0248] (7) Linear low density polyethylene film layer / polyurethane-based adhesive layer / biaxially oriented polyamide film layer / anchor coating layer / inorganic thin film layer / polyurethane-based adhesive layer / linear low density polyethylene film layer / low density polyethylene / paper / low density polyethylene / linear low density polyethylene film sealing layer.
[0249] (8) Biaxially oriented polyamide film layer / anchor coating layer / inorganic thin film layer / inorganic thin film protective layer / printing layer / polyurethane-based adhesive layer / unstretched polypropylene film sealing layer.
[0250] (9) Biaxially oriented PET film layer / inorganic thin film layer / inorganic thin film protective layer / printing layer / polyurethane-based adhesive layer / biaxially oriented polyamide film layer / polyurethane-based adhesive layer / easily peelable unstretched polypropylene film sealing layer.
[0251] Industrial Applicability
[0252] The biaxially oriented polyamide film of the present invention is excellent in impact resistance, flexing pinhole resistance, and friction pinhole resistance at the same time, and thus can be suitably used for applications such as food packaging materials. In addition, since a resin obtained by polymerizing a raw material derived from biomass originally present on the ground is used, it is a carbon-neutral film, and from the viewpoint of having little influence on the increase and decrease of carbon dioxide on the ground, it is possible to reduce the environmental load.
Claims
1. A method for producing a biaxially stretched polyamide film, characterized in that: include: A step of melt-extruding a raw material resin for a substrate layer (A) and a raw material resin for a surface layer (B) to obtain an unstretched film having the surface layer (B) laminated on at least one surface of the substrate layer (A); and A stretching step of stretching the unstretched film in the MD direction at 50° C. to 120° C. and then in the TD direction at 50° C. to 190° C., The substrate layer, i.e., layer A, contains 99% to 70% by mass of a polyamide 6 resin and 1% to 30% by mass of at least one polyamide resin selected from the group consisting of polyamide 11, polyamide 610, and polyamide 1010. The surface layer, i.e., layer B, contains 70% by mass or more of polyamide 6 resin, The thickness of the substrate layer (layer A) is 70 to 93% of the total thickness of the substrate layer (layer A) and the surface layer (layer B).
2. The method according to claim 1, wherein: After the stretching step, a heat fixing step is also included.
3. The method according to claim 2, wherein: The temperature of heat setting is set to 210° C. or higher and 220° C. or lower.
4. The method according to claim 2, wherein: The heat fixation time is set to 0.5 seconds to 20 seconds.
5. The method according to claim 1, wherein: The raw material resin of the substrate layer, ie, layer A, and the raw material resin of the surface layer, ie, layer B, are co-extruded at 220°C to 350°C.
6. The method according to claim 2, wherein: After the heat setting step, the method further includes a relaxation step at a heat setting temperature of -10°C to Tg+10°C.
7. The method according to claim 6, wherein: The relaxation rate of the relaxation treatment is set to 0.5% or more and 20% or less.
8. The method according to claim 1, wherein: The biaxially stretched polyamide film satisfies the following a and b: a: The number of Gabor pinhole defects when a torsional bending test is performed 1000 times at a temperature of 1°C using a Gabor torsion tester is 10 or less; b: The distance until a pinhole is generated in the friction pinhole resistance test is 2900 cm or more.
9. The method according to claim 1, wherein: The biaxially stretched polyamide film has a haze of 10% or less.
10. The method according to claim 1, wherein: The dynamic friction coefficient of the biaxially stretched polyamide film is 1.0 or less.
11. The method according to claim 1, wherein: The lamination strength after the biaxially stretched polyamide film and the polyethylene-based sealing film are bonded together is 4.0 N / 15 mm or more.
12. A method for manufacturing a packaging bag, characterized in that: include: A process for producing a biaxially stretched polyamide film by the method according to any one of claims 1 to 11; a step of laminating a sealing film on the biaxially stretched polyamide film to obtain a laminated film; and The laminated film is processed into a packaging bag.
13. The method according to claim 12, wherein: The sealing film is an unstretched linear low-density polyethylene film, an unstretched polypropylene film or an ethylene-vinyl alcohol copolymer resin film.
Citation Information
Patent Citations
Polyamide laminated film
JP1999254615A
Laminate having excellent pinhole resistance and packaging bag using it
JP2001205761A
Polyester resin composition
JP2012097163A
Stretched polyamide film
CN103402737A
Biaxilly oriented polyamide film and its production process
US5612105A